Regulatory Mechanism of ITGBL1 in the Metastasis of Colorectal Cancer - Qi, Lu; Song, Fuyao; Ding, Yanqing (Frontiers in Oncology, 2020)
Abstract: Integrin, beta-like 1 (ITGBL1) is located in extracellular matrix (ECM) and involved in the development and metastasis of many tumors. However, the regulatory mechanism of ITGBL1 in colorectal cancer (CRC) remains unclear. This study analyzed the expression profile of CRC and identified the expression change of ITGBL1 gene in different staging of CRC. Survival analysis showed that ITGBL1 was related with the metastasis of CRC and CRC patients with high expression of ITGBL1 had earlier metastasis. GESA enrichment analyzed the relationship between ITGBL1 expression and molecular events of CRC. It was found that, high expression of ITGBL1 was linked to Wnt signaling pathway, cell polarity and tissue development while low expression of ITGBL1 was related with cellular respiration, electron transfer chain and oxidative phosphorylation. Based on the interstitial and parenchyma CRC expression profiles, a comparison was made to determine the difference between high/low expression of ITGBL1 and Wnt signaling pathway, respectively, and further confirmed the close relation between ITGBL1 and Wnt signaling pathway. For determining the relation, an interaction network of ITGBL1 and Wnt signaling proteins was constructed. It was found that β-catenin interacted with multiple extracellular Wnt signals and could bind to ITGBL1. As a result, the regulatory mechanism of ITGBL1 in CRC was related to extracellular Wnt signals and may affect extracellular Wnt signals via β-catenin.